Stylized Reindeer Sculpture in Concrete and Steel - Campbell, Sandy (2018)
Two concrete and metal reindeer stand on the sidewalk outside of the City Hall in Rovaniemi, Finland. Constructed from large concrete forms, two arcs of metal tube on the head represent horns. Each reindeer has red and yellow stripes.